SPE Annual Technical Conference and Exhibition 2004
DOI: 10.2118/90396-ms
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Rotary Steerable System Bottomhole Assemblies Minimizes Wellbore Tortuosity and Increases Directional Drilling Efficiency

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Computer-based engineering models and further full scale laboratory drilling tests resulted in refinement of BHA configurations to deliver improved dogleg capability and more predictable directional performance (Stroud, Peach & Johnston, 2004). Several further reviews of both experimental lab and field data concluded that lateral bit stability is a dominant factor in the performance of this point-the-bit RSS (Barton, Pierce & Stroud, 2009).…”
Section: Evolution Of the Systemmentioning
confidence: 99%
“…Computer-based engineering models and further full scale laboratory drilling tests resulted in refinement of BHA configurations to deliver improved dogleg capability and more predictable directional performance (Stroud, Peach & Johnston, 2004). Several further reviews of both experimental lab and field data concluded that lateral bit stability is a dominant factor in the performance of this point-the-bit RSS (Barton, Pierce & Stroud, 2009).…”
Section: Evolution Of the Systemmentioning
confidence: 99%
“…An alternative method for drilling and controlling the trajectory of laterals is through the use of rotary steerable systems (RSS) (Rasheed et al, 2005;Stroud et al, 2004). An alternative method for drilling and controlling the trajectory of laterals is through the use of rotary steerable systems (RSS) (Rasheed et al, 2005;Stroud et al, 2004).…”
Section: Rotary Steerablementioning
confidence: 99%
“…To be compatible with the push-the-bit RSS, this bit must be run with a special ledge trimming sub. Alternatively, a tricone bit with lug pads can be used to increase lateral stability of the bit as reported by Stroud et al 16 .…”
Section: Bit E (Tricone Bit)mentioning
confidence: 99%